What on Earth is geodiversity? - Helena Tukiainen; Maija Toivanen (Nordia Geographical Publications)
The concept of geodiversity is gaining recognition in many scientific fields, as well as in practical applications such as conservation and tourism. Although the importance of geodiversity is now widely accepted, its precise definition, scope and broader applicability continue to be debated and discussed. In this paper, we explore the variety of viewpoints that relate to geodiversity and scrutinize the importance of geodiversity for different audiences. These viewpoints include definitions, assessment, research fields, terminology and its applications. To help explore and convey the different viewpoints and values commonly attributed to geodiversity, we invoke the Rokua UNESCO Global Geopark in Finland as a specific case study. Finally, we present potential future directions for geodiversity research, including key knowledge gaps, and highlight the vulnerability of geodiversity to increasing human pressures that threaten its integrity and long-term sustainability.